Influence of black sigatoka disease on the growth and yield of diploid and tetraploid hybrid plantains - Craenen, K.; Ortíz, R. (Elsevier, 1998)
Plantain and banana (Musa spp.) are important staple food crops in the humid forest and mid-altitude agro-ecologies of sub-Saharan Africa. Black Sigatoka, caused by Mycosphaerella fijiensis, is an airborne fungal disease which attacks the leaves of the Musa plant. It is commonly considered the major constraint to plantain production in West Africa. The disease causes severe leaf necrosis and reduces yield by 30 to 50%. Twenty euploid hybrids, derived from interspecific interploidy crosses were selected for a range of host responses to black Sigatoka. The performance of these hybrids was compared with that of their parents to determine the influence of the disease on growth parameters and components of yield. There were significant differences for all components of black Sigatoka resistance, growth parameters, and yield components among the hybrids. For diploid hybrids, which often had a short growth cycle, early flowering, or both, the disease incubation time was significantly correlated with days to fruit filling (P<0.05). However, for tetraploid hybrids that had a long growth cycle and delayed flowering, the correlation was not significant (P ≥ 0.05). For diploid and tetraploid hybrids, the disease evolution time and the disease development time were both correlated (P < 0.05) with days to fruit filling. The bunch weight of tetraploid hybrids was correlated (P < 0.05) with the disease development time that was easily scored by the youngest leaf spotted at flowering (ρ = 0.933; P < 0.001). Hence, black Sigatoka resistant hybrids with potential high yield could be selected efficiently by recording the youngest leaf spotted at flowering.